Fixed point index theory for decomposable multivalued maps and applications to discontinuous ϕ-Laplacian problems. (October 2020) - Precup, Radu; Rodríguez-López, Jorge
Abstract: In this paper, we develop a fixed point index theory for decomposable multivalued maps, that is, compositions of two multivalued nonlinear upper semicontinuous maps. As an application, this fixed point index theory is combined with the method of lower and upper solutions in order to obtain new existence, localization and multiplicity results for ϕ -Laplacian problems with discontinuous nonlinearities and nonlinear functional boundary conditions.